The history of the occupation of land in the Cape Colony and its effect on land law and constitutionally mandated land reform - Brand, Danie (Jacobus Frederick Daniel, 1968- ) (University of Pretoria, 2019)
Thesis (LLD)--University of Pretoria, 2018.